Restatement of the Law, Copyright: A Useful Resource for Practitioners and Courts or a Rashomon Exercise? - Schwartz, Eric J. (The Columbia Journal of Law & the Arts, 2021)
As the Ninth Circuit succinctly observed, when deciphering copyright law, “[w]e begin, as always, with the text of the statute.” An examination of any aspect of copyright law commences with the text of Title 17 of the United States Code (the “statute”), and then turns to case law for adjudications and interpretations of the relevant statutory text, or as the primary source of law in the gaps in the statute. Everything else is secondary and not, of course, a substitute for the law, whether it is legislative history, Copyright Office (and other government agency) studies, treatises, or other commentary. If copyright law consists predominantly of federal statute, how, if at all, will the American Law Institute (“ALI”) project to prepare a Restatement of the Law of Copyright (the “Restatement”) provide a useful or necessary resource for attorneys and the courts? In the face of the primacy of the enacted statutory text, why undertake a project to recast and rephrase the law? What, if any, use might it yield to practitioners and courts, and equally importantly, will consequential harms result? From the inception of the Restatement project, the creative community has collectively viewed the project with skepticism about its necessity and fears about its purpose and biases, and the resultant impact on the livelihoods of creators. This Response focuses on the practical uses, if any, of the Restatement for attorneys and courts grappling with copyright issues. The Response also examines, from a practitioner’s point of view, the Restatement’s potential to harm the ecosystem of the copyright creative community, and the likelihood that the harm will outweigh any value the Restatement might bring to clarifying the law.